Thymol maintains peppers quality by regulating antioxidant capacity, cell wall metabolism and membrane lipid metabolism - Xue Li; Xiaogang Wang; Jianye Chen; Donglan Luo; Sen Cao; Liangjie Ba (Food Chemistry: X)
This study investigates the effect of 100 mg L−1 thymol treatment on the quality of post-harvest peppers stored at 10 °C. The results showed that thymol treatment significantly reduced decay rate, reactive oxygen species (ROS) accumulation, and saturated fatty acid levels in peppers. Moreover, unsaturated fatty acids, non-enzymatic antioxidants, and antioxidant enzyme levels increased after treatment. For example, catalase (CAT) activity rose by 1.29-fold at 18 d, while ascorbic acid (AsA) content increased by 3.38-fold at 36 d. Additionally, thymol application inhibited the hydrolysis of pepper cell wall components and decreased the activities of enzymes related to cell wall and membrane lipid metabolism. Specifically, cellulase and lipase treatments showed reductions of 26 % and 1.73-fold compared to control (CK) at 36 d; protopectin (PP) also exhibited a 1.2-fold increase relative to CK. In conclusion, thymol can maintain antioxidant activity under post-harvest conditions while slowing cell wall and lipid metabolism processes.